1989
DOI: 10.1159/000129010
|View full text |Cite
|
Sign up to set email alerts
|

Primate Cardiac Allo- and Xenotransplantation: Modulation of the Immune Response with Photochemotherapy

Abstract: Survival of heterotopic allo- and xenografts was studied in a primate cardiac transplantation model. Initially, animals were presensitized to donor xenoantigens by blood transfusion and treated with strategies designed to elicit pretransplant immunosuppression. These animals underwent rapid rejection whether treated with ciclosporin and conventional immunosuppression, autologous sera, sensitized lymphocytes, or photochemotherapy. In a nonsensitized xenograft study, xenografts were maintained for prolonged peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Experimentally, photoinactivation of splenocytes with psoralen and UV-A light suppresses the induction of GVHD in mice 4,5 but there are no data on the treatment of GVHD as such. Others studies have shown that infusions of photoinactivated antidonor T cells resulted in a prolonged retention of skin or organ allogeneic grafts, 6,7 suggesting the development of an immune reaction responsible for the downmodulation of allogeneic reactive T-cell function. In vivo production of immunosuppressive cytokines by macrophages or monocytes, following ingestion of apoptotic cells, has been suggested as a general immune effect of ECP.…”
mentioning
confidence: 99%
“…Experimentally, photoinactivation of splenocytes with psoralen and UV-A light suppresses the induction of GVHD in mice 4,5 but there are no data on the treatment of GVHD as such. Others studies have shown that infusions of photoinactivated antidonor T cells resulted in a prolonged retention of skin or organ allogeneic grafts, 6,7 suggesting the development of an immune reaction responsible for the downmodulation of allogeneic reactive T-cell function. In vivo production of immunosuppressive cytokines by macrophages or monocytes, following ingestion of apoptotic cells, has been suggested as a general immune effect of ECP.…”
mentioning
confidence: 99%
“…20 After this initial success, recent trials in humans have similarly shown the reversal of acute cardiac allograft rejection. 21,22 This range of indications for photopheresis has now been expanded to include prophylactic treatment immediately after heart transplantation [23][24][25] and rescue therapy for severe racalcitrant cardiac allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The first reports of ECP in solid-organ rejection appeared in 1989 in animal models of transplantation after the recognition that allograft rejection involves clonal expansion of activated T-cells [18,19]. The expansion in the indications for ECP that ensued in the decade that followed will be discussed below.…”
Section: What Is Ecp and Why Is It An Option In Heart And Lung Transpmentioning
confidence: 99%